Virtue Ethics and the Selection of Children with Impairments A Reply to Rosalind McDougall - Saenz, Carla (2010)
In “Parental Virtues: A New Way of Thinking about the Morality of Reproductive Actions” Rosalind McDougall proposes a virtue-based framework to assess the morality of child selection. Applying the virtue-based account to the selection of children with impairments does not lead, according to McDougall, to an unequivocal answer to the morality of selecting impaired children. In “Impairment, Flourishing, and the Moral Nature of Parenthood,” she also applies the virtue-based account to the discussion of child selection, and claims that couples with an impairment are morally justified in selecting a child with the same impairment. This claim, she maintains, reveals that the flourishing of a child should be understood as requiring environment-specific characteristics. I argue that McDougall’s argument begs the question. More importantly, it does not do justice to virtue ethics. I also question to what extent a virtue ethics framework can be successfully applied to discussions about the moral permissibility of reproductive actions.